Pippa's Persona in Holly Jackson A Good Girl's Guide To Murder - Titaley, Reyhan Humaira; Marsih, Linusia (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2025)
This study seeks to analysis Pippa Fitz-Amobi’s persona archetype in A Good Girl’s Guide To Murder (2019) by Holly Jackson. Jung stated that persona is a mask used to show a different side of a person’s personality to the public which are friendly, kind, wise, and competent personalities. Designing a qualitative method with psychoanalysis approach of Jung’s persona archetypes. The study found that Pippa’s persona is friendly, kind, wise, and competent which are reflected when Pippa uses her friendly to behave in a pleasant and makes other happy and comfortable in the social interaction. Her wisdom helps her make good consideration before giving judgments to others. Further, her kindness is to help others and to be emphaty about other people’s feelings. Last, Pippa uses her competence showed by her having skills or knowledge to investigate the case in finding the evidences and information from her society that is friend, teacher, journalist, and police. Pippa is able to be a good girl for her society her desire to prove that Salil Singh is not guilty.